Improving heterologous membrane protein production in Escherichia coli by combining transcriptional tuning and codon usage algorithms. - Nico J Claassens; Melvin F Siliakus; Sebastiaan K Spaans; Sjoerd C A Creutzburg; Bart Nijsse; Peter J Schaap; Tessa E F Quax; John van der Oost (PLoS ONE)
High-level, recombinant production of membrane-integrated proteins in Escherichia coli is extremely relevant for many purposes, but has also been proven challenging. Here we study a combination of transcriptional fine-tuning in E. coli LEMO21(DE3) with different codon usage algorithms for heterologous production of membrane proteins. The overexpression of 6 different membrane proteins is compared for the wild-type gene codon usage variant, a commercially codon-optimized variant, and a codon-harmonized variant. We show that transcriptional fine-tuning plays a major role in improving the production of all tested proteins. Moreover, different codon usage variants significantly improved production of some of the tested proteins. However, not a single algorithm performed consistently best for the membrane-integrated production of the 6 tested proteins. In conclusion, for improving heterologous membrane protein production in E. coli, the major effect is accomplished by transcriptional tuning. In addition, further improvements may be realized by attempting different codon usage variants, such as codon harmonized variants, which can now be easily generated through our online Codon Harmonizer tool.